Developmental psychology for teachers : an applied approach - McInerney, D. M. (Dennis M.), 1948- (Crows Nest, N.S.W. : Allen & Unwin, 2006)
Offers a thorough introduction to the aspects of human development, which are of most importance in the classroom. Dennis McInerney outlines the stages of physical, motor and cognitive development from birth to early adulthood, explaining the relationship between heredity and environment.
Preface
1: Developmental psychology: Themes and research
2: Heredity, environment and special learning needs
3: Physical and motor development: Infancy to late childhood
4: Physical and motor development: Puberty to adulthood and development health issues
5: Cognition and cognitive development: Infancy to late childhood
6: Cognitive development: Adolescence to adulthood
7: Conceptions of intelligence and creativity in childhood and adolescence
8: Cognition and information processing in childhood and adolescence
9: Personal and social development in childhood
10: Personal and social development in adolescence
11: Moral development in childhood and adolescence
Glossary of key terms
References and further reading
Index
Bibliografija: str. 360-398.
Kazalo
Keywords: Developmental psychology; Educational psychology; razvojna psihologija; psihologija obrazovanja